PENGARUH KONSENTRASI PUTIH TELUR TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK SARI BUAH PALA (Myristicafragrans Houtt) - F., Shanly Vivia; Trsinawati, Chatarina Yayuk; Budianta, Dwi Wibawa (Jurnal Teknologi Pangan dan Gizi, 2014)
The aim of research was to determine the effect of egg white concentration on physicochemical and sensory properties of nutmeg fruit juice. Randomized Block Design was used in this research with factor namely egg white concentration that consisted of six levels (0%, 1%, 2%, 3%, 4%, 5%). Each level was replicated four times. Parameter tested were pH, titratable acidity, precipitate percentage and sensory (preference of appearance, colour, and taste). Data were be analyzed with Analysis of Variance (ANAVA) (α= 5%). If ANAVA showed a significant effect, it was followed by Duncan’s Multiple Range Test (α= 5%). The results showed that egg white concentration significantly affected on pH, titratable acidity and precipitate percentage. The higher egg white concentration, pH value and the percentage of precipitation increased, but titratable acidity decreased. pH value ranged from 3.20- 3.32, titratable acidity value ranged from 71 mL NaOH 0.1N/ 100 mL – 80.92 mL NaOH 0,1N/ 100 mL, the percentage of precipitation ranged from 2.09% - 14.73%. Egg white concentration also significantly affected on the appearance that ranged from 4.71-5.87 (rather do not like – rather like) and taste preferences ranged from 5.09-5.79 (neutral – rather like), but did not significantly affect colour preferences thar ranged from 5.02- 5.33 (neutral – rather like).